2014
DOI: 10.1519/jsc.0000000000000495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Training Amplitudes on Heart Rate and Heart Rate Variability in Young Rowers

Abstract: The aim of this study was to investigate the autonomic nervous system recovery and the psychological response as a result of 3 training amplitudes on heart rate (HR), heart rate variability (HRV), and rate of perceived exertion (RPE) in rowing. Eight young rowers (16.8 ± 1.4 years) performed, in a randomized fashion, 2 sessions of high-intensity interval training, with high and low amplitude and a continuous training (CT) session, with the same exercise duration (10 minutes) and mean intensity (60% of maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, the volume of oxygen, the heart rate and the lactate concentration were not different between these different conditions. Other articles compared the variation of heart rate with training of different intensities (Vaz, Picanço, & Del Vecchio, 2014). This study concluded that ALFONSO PENICHET-TOMÁS, JOSÉ MANUEL JIMÉNEZ-OLMEDO, BASILIO PUEO, JOSÉ…”
Section: Introductionmentioning
confidence: 75%
“…However, the volume of oxygen, the heart rate and the lactate concentration were not different between these different conditions. Other articles compared the variation of heart rate with training of different intensities (Vaz, Picanço, & Del Vecchio, 2014). This study concluded that ALFONSO PENICHET-TOMÁS, JOSÉ MANUEL JIMÉNEZ-OLMEDO, BASILIO PUEO, JOSÉ…”
Section: Introductionmentioning
confidence: 75%
“…Such finding is in line with the data found in this study, since the HR did not present significant changes between the conditions. These outcomes may have resulted from the implementation of oxygen restriction associated with the short period of effort and prolonged rest, which is likely to have not been sufficient to generate differences and resulted in a predominance of the sympathetic nervous system in relation to the parasympathetic, in both conditions similarly (Vaz et al, 2014). Meeuwsen et al (2001) conducted a study with 16 subjects randomized into two groups: one with hypoxia training (simulated altitude of 2500 m) and the other without, both with intensities between 60 and 70%.…”
Section: Discussionmentioning
confidence: 99%
“…When taken all-together, such fluctuations of HR in postexercise recovery (reaching + 17 or -15 bpm) are more meaningful for training load evaluation and autonomic activity monitoring than short-term (2 min post-exercise recovery) HRV indices (RMSSD) unlike proposed for longterm (1 to 24 hours post-exercise) HRV indices (Cipryan, Laursen, & Plews, 2016;Vaz, Picanco, & Del Vecchio, 2014). From a health perspective, downhill HIIT appeared to acutely and chronically allow a better HRV profile, which perhaps would be of interest for health applications of HIIT.…”
Section: Resultsmentioning
confidence: 99%